Vortical flow structures induced by red blood cells in capillaries. (18th March 2021) - Yaya, François; Römer, Johannes; Guckenberger, Achim; John, Thomas; Gekle, Stephan; Podgorski, Thomas; Wagner, Christian
Abstract: Objective: Knowledge about the flow field of the plasma around the red blood cells in capillary flow is important for a physical understanding of blood flow and the transport of micro‐ and nanoparticles and molecules in the flowing plasma. We conducted an experimental study on the flow field around red blood cells in capillary flow that is complemented by simulations of vortical flow between red blood cells. Methods: Red blood cells were injected in a 10 × 12 µm rectangular microchannel at a low hematocrit, and the flow field around one or two cells was captured by a high‐speed camera that tracked 250 nm nanoparticles in the flow field, acting as tracers. Results: While the flow field around a steady "croissant" shape is found to be similar to that of a rigid sphere, the flow field around a "slipper" shape exhibits a small vortex at the rear of the red blood cell. Even more pronounced are vortex‐like structures observed in the central region between two neighboring croissants. Conclusions: The rotation frequency of the vortices is to a good approximation, inversely proportional to the distance between the cells. Our experimental data are complemented by numerical simulations.